The Relationship Between Self Care Behavior and Quality of Life of Breast Cancer Patients Undergoing Chemotherapy in The Chemotherapy Room of Bali Mandara Hospital - Ni Nyoman Mariathi; Ida Ayu Agung Laksmi; Ni Putu Cyntia Maseni (Jurnal Kesehatan, 2025)
Introduction: Breast cancer patients with chemotherapy treatment have a negative impact on physical and psychological quality of life. This impact can be influenced by self care behavior. This study aims to determine the relationship between Self Care Behavior and the quality of life of breast cancer patients undergoing chemotherapy in the Chemotherapy Room of Bali Mandara Hospital Method: The study was conducted with an analytical observational design with a cross sectional approach conducted from February to March 2025 with a total sample of 34 respondents selected by purposive sampling technique. Data were collected using the Self Care Behavior questionnaire and the ORTC QLQ BR-23 questionnaire. Data were analyzed using the spearman's rho test. Results: The results showed that the majority had self care behavior dependence as much as 67.6% and most of the functional quality of life and symptoms in the moderate category as much as 73.5%. Analysis of the relationship between self care behavior and the quality of life of breast cancer patients undergoing chemotherapy in the Chemotherapy Room of Bali Mandara Hospital obtained a p value <0.001. Conclusion: It can be said that there is a relationship between self care behavior and the quality of life of breast cancer patients undergoing chemotherapy in the Chemotherapy Room of Bali Mandara Hospital. The recommendations of this study are expected to be input for nurses to always provide counseling to patients with diabetes mellitus to improve quality of life. Protocol registration: This research has previously passed ethical review with the number: 015/EA/KEPK.RSBM.DISKES/2025